Factors affecting human behaviour towards fire safety in residential college. case study : UiTM Seri Iskandar / Mohamad Azim Kamaruzzaman and Najma Azman - Kamaruzzaman, Mohamad Azim; Azman, Najma (2019)
Human behaviour in fire is a new study that many researcher try solve compare to others study areas. Recently, the research based on human behaviour in fire has begun to flourishing. The objectives of this research are to identify the factors affecting human behaviour in fire safety as well as to find the significance of students’ background and human behaviour towards fire safety in residential colleges. Factors affecting human behaviours being collected from secondary data mainly from journas, books, reports, articles, internet and presented into a conceptual framework. A set of questionnaire being developed and posted to 250 respondents to complete the survey. The statistical packages for the social science (SPSS) Version 22 is being used to run the results. Based on the findings the attitude, personality, beliefs and values ranking in order, have show positive significant with the student background where P-value is less than 0.05.